Perceptions regarding childhood immunization among mothers in Kunnukara Panchayat, North Paravur, Ernakulam, Kerala - Kuruvilla, Babita Susan; Cherian, Vinu; Thomas, Ann Mary; Rose, Brilly M.; John, Alexander (International Journal Of Community Medicine And Public Health, 2021)
Background: Vaccines have been claimed to be one of the most important contributions for the relief of human misery and the spectacular increase in life expectancy. Worldwide, an estimated 1.4 million children under the age of five died in 2010 due to vaccine preventable diseases. Objective of the study was to determine the immunization perception and practice regarding immunization among mothers of children from 1-5 years in Paravur taluk, Ernakulam district. Methods: This cross-sectional study was done among the mothers of children from 1-5 years of age in Kunnukara panchayat. The panchayat has 15 wards. 3 wards were chosen by simple random sampling. All the houses having mothers of children from one to five years were surveyed. The data collected was entered in MS excel and analysed using Statistical package for social sciences (SPSS) 20 software. Results: Mean age of mothers is 29. The most common source of information regarding vaccination was obtained through health workers (80.3%). 72% mothers knew that OPV prevents polio and 53.6% mothers knew about the frequency of giving polio vaccination to their children. Ninety two percent mothers agreed that vaccines prevent the diseases. 100% mothers have given immunization to their children. Conclusions: Perception regarding vaccination was 95.2% and practice of immunization was 92.3%. There was a statistically significant association between (female gender of child v/s practice of immunization) and (perceptions regarding vaccination v/s practice of immunization).